Level of Understanding of Sports Injury Management With T.O.T.A.P.S METHOD Among Members of the Student Activity Unit Futsal at Universitas Mercu Buana Yogyakarta - Simamora, Wilson Sotar Dodo; Saptro, Yulius Agung (Education Achievement: Journal of Science and Research, 2024)
This study aims to determine the level of understanding of handling sports injuries using the T.O.T.A.P.S method among members of the Futsal Student Activity Unit (UKM) at Mercu Buana University, Yogyakarta. This type of research uses qualitative descriptive research conducted using a survey method distributed via Google Form. There were 51 members of UKM Futsal UMBY who were the samples in this research. To calculate the percentage included in the category in each aspect, the formula is used, namely: P = F/N x 100%. The results of this study concluded (1) understanding of the factors that cause sports injuries in the "Understand" category amounted to 31 people (60.8%) in the "Very Understand" category 16 people (31.4%) in the "Don't Understand" category 4 people (7 .84%), (2) understanding of basic sports injury management in the "Understand" category totaling 31 people (60.8%) in the "Understand" category totaling 31 people (60.8%) in the "Very Understand" category 18 people (35 .3%) in the "Don't Understand" category 2 people (3.92%), (3) understanding of handling sports injuries using the T.O.T.A.P.S method in the "Understand" category totaling 32 people (62.7%) in the "Very Understand" category 18 people ( 35.3%) category "Don't Understand" 1 person (1.96%). The research results show that the level of understanding of handling sports injuries using the T.O.T.A.P.S method among members of the Futsal Student Activity Unit (UKM) at Mercu Buana University, Yogyakarta is "understand".